2005
DOI: 10.1128/jcm.43.9.4592-4601.2005
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characteristics of Streptococcus porcinus Isolated from Human Sources

Abstract: The phenotypic and genotypic characteristics of 25 Streptococcus porcinus isolates recovered from human sources were investigated and compared to the characteristics of 17 reference strains obtained from nonhuman sources. All of the S. porcinus isolates were beta-hemolytic (wide zones), susceptible to vancomycin, gave positive results for the leucine aminopeptidase and L-pyrrolidonylarylamidase tests, and produced acids from mannitol and sorbitol. Most of them were positive for the CAMP test and resistant to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 24 publications
4
29
0
Order By: Relevance
“…Therefore, based on some of these findings, it has been suggested that S. pseudoporcinus may be associated with sexually transmitted infections (STIs). S. pseudoporcinus is exquisitely susceptible to beta-lactam antibiotics, vancomycin, and trimethoprim-sulfamethoxazole but has a high rate of resistance to tetracycline (1,3,7). Although some isolates of S. pseudoporcinus are resistant to erythromycin and clindamycin, significantly higher rates of resistance have been observed with S. agalactiae (1,3,5,7).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, based on some of these findings, it has been suggested that S. pseudoporcinus may be associated with sexually transmitted infections (STIs). S. pseudoporcinus is exquisitely susceptible to beta-lactam antibiotics, vancomycin, and trimethoprim-sulfamethoxazole but has a high rate of resistance to tetracycline (1,3,7). Although some isolates of S. pseudoporcinus are resistant to erythromycin and clindamycin, significantly higher rates of resistance have been observed with S. agalactiae (1,3,5,7).…”
Section: Discussionmentioning
confidence: 93%
“…In 2005, Duarte et al used randomly amplified polymorphic DNA-PCR and pulsed-field gel electrophoresis analyses to show that these human isolates differed from isolates obtained from animal sources, with the majority of the human strains containing NG1 antigen (3). Subsequently, analysis of 16S rRNA gene sequence data of several human isolates recovered from female genitourinary tract specimens phenotypically described as S. porcinus revealed the sequences to be Ͼ2% dissimilar to any other Streptococcus species and thus highly suggestive of a novel species (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptococcus viridans and Streptococcus mitis/oralis are commensal bacteria in the oral cavity and gastrointestinal tract 11. Other blood culture revealed the growth of Streptococcus porcinus , a member of beta hemolyticus streptococcus originating from genitourinary tract of female in reproductive age 12. Single bacterial growth from blood culture of polymicrobial IE may result from growth competition in blood agar media.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, they considered a detailed analysis of gel data by using high-resolution densitometers and software. Three groups of bacterial isolates belonging to Acromobacter, Neisseriaceae and Providencia were analyzed by this method, and subsequently the strategy of 1-D protein electrophoresis was widely used for typing of a number of bacterial isolates such as Streptococcus porcinus, Bacillus thuringiensis, Helicobacter pylori, etc (Duarte et al, 2005;Konecka et al 2007;Costas et al, 1990). The Haemophilus influenzae proteome was analyzed by 2-DE and extended to three other members of the Haemophilus genus in 1997.…”
Section: Microbial Systematics and Epidemiologymentioning
confidence: 99%